High‐density planting with lower nitrogen application increased early rice production in a double‐season rice system. (22nd January 2020) - Zheng, Huabin; Chen, Yuanwei; Chen, Qimin; Li, Bo; Zhang, Yansheng; Jia, Wei; Mo, Wenwei; Tang, Qiyuan
Abstract: High‐density planting is a strategy employed to save resources in crop production, particularly in environmentally friendly double‐season rice ( Orvza sativa L.) cropping, where it promotes high grain yield and reduces required nitrogen (N) input. We conducted a field experiment in 2014–2018 to detect the combined effect of increased seedling density and reduced N input on early rice grain yield and N use efficiency (NUE). The higher basic seedling with low N input treatment (T2) had an average grain yield of 7.01 t ha −1, which was 16.3% greater than that of the control (CK). There was a strong linear relationship between grain yield and panicles m −2 ( R 2 = .82, P < .001). Grain yield increased significantly with above‐ground biomass before the full‐heading stage ( R 2 = .79, P < .001), which in turn promoted an increase in panicles m −2 ( R 2 = .85, P < .001). Mean agronomic efficiency (AE) in the T2 treatment was 34.3 kg kg −1 N, which was 48.1% higher than that in the CK treatment. Therefore, increasing seedling density from 62.5 to 176 seedlings number m −2 while reducing inorganic N input in the early season resulted in significantly higher grain yield in hand‐transplanted rice production. Our results indicate that dense planting with N reduction could improve early rice grain yield and enhance NUE.